Spiraling up and down: Mapping women's empowerment through agricultural interventions using the community capitals framework in rural Ethiopia. Issue 1 (1st January 2021) - Mulema, Annet Abenakyo; Boonabaana, Brenda; Debevec, Liza; Nigussie, Likimyelesh; Alemu, Mihret; Kaaria, Susan
ABSTRACT: The paper draws on the Community Capitals Framework to frame and analyze the process of rural women's empowerment through agricultural interventions in two districts of Ethiopia. A blend of qualitative data collection methods comprising group discussions, life histories, and key informant interviews was used. Our study shows that investing in social, human, financial, cultural, natural, physical, and political capitals resulted in increased assets within those capitals and others amongst the beneficiaries. The interaction between capitals builds "power with", "power within", "power to" and "power over" in an upward spiral. Specifically, the interaction between social, human and financial capitals is a key entry point to rural women's empowerment. Cultural capital intermediates the interaction and flow of capital assets during the empowerment process. We argue that empowering women requires an approach that enhances their capability to identify and systematically manage interactions among capitals that foster their voice and agency.